Exploring ESL students’ experiences of academic writing in higher education- a cultural historical activity theory perspective - Naureen Rahnuma (Education Inquiry, 2023)
ABSTRACTWriting in discipline and across the curriculum as an academic literacy practice has been the subject of a growing body of research in HE over the past few decades. In Bangladesh, however, effective academic writing in English as a second language (ESL) is an interminable challenge for tertiary students. This study uses a sociocultural theoretical lens by applying a CHAT framework to develop an in-depth, contextualised understanding of how Bangladeshi HE students engage with writing in an ESL setting while collaborating among individual learners and their social learning contexts. Drawing on data collected from in-depth interviews, the paper elucidates how learners construct subjective accounts of their perception of academic writing in HE and identifies six contradictions in their writing trajectory. In conclusion, the implications of utilising a CHAT framework as a reflective tool to re-evaluate, re-envision and remodel learning activity systems while steering interventions at micro, meso and macro-level policymaking to enhance expansive learning are discussed.